(untitled) (Fiep Bulletin - online, 2024)
Introduction: The burnout or syndrome of being burned, is the response that a worker gives when he perceives the difference between his own ideals and the reality of his working life, generally developing in the helping professions and frequent social interrelation. Saborío & Hidalgo (2015). Objective: is to analyze the impact of burnout syndrome in recreational physical activities. Methods: Type of quantitative, correlational and cross-sectional research (June to December 2022); Where 179 workers participated belonging to the Public Security Secretary of the State of Durango, Mexico. (C5), (86 men and 93 women) of an age of 25 to 50 years old, where the exclusion factors were Subjects who do not wish to participate, who have some motor impediment that prevents them from performing physical activities.. Results: according to the perception of the subjects, the level of work stress decreases significantly from the implementation of recreational physical activities, as well as the increase in the level of job satisfaction. Conclusion: it is important to establish recreational physical activities that contribute to the reduction of work stress and with it, a better work environment where they feel valued for the performance of their duties in daily tasks Keywords Burnout Syndrome, Work Performance, physical activity